Review of Ethnological Research on Slovene Emigration - Čebulj Sajko, Breda (Two Homelands, 1993)
Unlike similar descriptions of ethnological research on Slovene emigration, in this paper the author devotes attention to an explanation of the methodological orientation in past research on this topic. In a historical cross-section of the post-Second World War interest on the part of Slovene ethnologists in the issue of emigration, a blossoming in this area can be noticed in the eighties, while due to the meagre number and lack of interest of researchers, such enthusiasm is today fading. The article is accompanied by an extensive, yet still selective, bibliography which notes some encouragement for the research of Slovene emigration in the period prior to 1940.